When Nudges Backfire: A Distinction Between Spillovers and Misfires - Themistocleous, Christos; Karapanos, Evangelos (My University, 2026)
The concept of nudging (libertarian paternalism) has been eagerly adopted in the design of digital behavioural interventions, yet discussion on adverse effects of nudges has been limited. In an attempt to enhance resolution, this theoretical paper conceptually differentiates two types of adverse effects, namely, spillovers and misfires. We propose that contrary to behavioural spillovers that occur as a consequence of a targeted behaviour, the causality of misfires is primarily attributed to the nudge type. In doing so, we employ visual representations of the behavioural trajectories that demonstrate intended and unintended effects of nudges to support choice architects in blueprinting intervention processes. We differentiate between spillovers and misfires by summarizing key empirical research that seeks to explain the causes of each and the contextual nature that distinguishes them. We conclude by drawing implications for the design of technology-mediated nudges as well as the role of its timing.
Keywords: Behavioural Spillover; Behavioural Pathway; Libertarian Paternalism; Nudge Misfire; Nudge Theory